Litter fall production in a native forest in Depression Central region-RS - Vogel, Hamilton Luiz Munari; Lorentz, Leandro Homrich; Oliveira, Fabriciane Pereira (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
The present study aimed to quantify the annual litter fall and seasonality , in a fragment of native forest located in the Central Depression of Rio Grande do Sul, in São Sepé. The experiment was conducted in a fragment of Seasonal Semideciduous Forest. Inside this forest, in a place with homogeneous conditions were systematically allocated five plots of 20 m x 15 m length, 30 meters away from each other, which were distributed five collectors in each plot, totaling 25 collectors. These were fixed in place to a height of one meter from the ground. The collection of all plant material deposited by the trees in the collectors was performed monthly. In the laboratory, the samples were separated into leaves, twigs (diameter < 0.5 cm) and miscellaneous , were oven dried and weighed on a precision balance. It was found for the analyzed period an average annual of 6.53 Mg ha-1 litter fall; this total accounted for 70% leaves, followed by miscellaneous with 18.6% and twigs with 11.4%. In the collection period of the study, there was a greater deposition of litter in the spring, especially in the months from October to January, with peak return in November.